Current Trends in Critical Discourse Studies of Textbooks: A Look at Selected Literature - Smith, Christopher; Sheyholislami, Jaffer (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée)

(untitled) (University of New Brunswick, 2022)
Critical discourse analysis (CDA) has increasingly served to examine the content of textbooks. Given momentum by critical social inquiry pertaining to textbook content, this study looks at peer-reviewed literature drawn from three scholarly databases (JSTOR, ERIC, and SAGE; cross-referenced with searches on Google Scholar) that use critical discourse analysis for those investigations. Reviewing the selected literature, this study asks: What are the most represented approaches of CDA used for examining textbooks? What contextual themes appear to draw the most attention? In what fields of study are the examined textbooks situated? How do these emergent themes appear to be connected? What areas of research appear lacking in the collected literature? The findings illustrate that, while the methods of CDA and types of textbooks examined are diverse, the lion’s share of contextual attention and critical utility appear to be given to foundational approaches to CDA and textbooks used for English language teaching. Further research directions on textbooks from a CDA perspective are discussed.